2011
DOI: 10.1136/gutjnl-2011-300843
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the Bowel Cancer Screening Programme (BCSP) in England after the first 1 million tests

Abstract: IntroductionThe Bowel Cancer Screening Programme in England began operating in 2006 with the aim of full roll out across England by December 2009. Subjects aged 60–69 are being invited to complete three guaiac faecal occult blood tests (6 windows) every 2 years. The programme aims to reduce mortality from colorectal cancer by 16% in those invited for screening.MethodsAll subjects eligible for screening in the National Health Service in England are included on one database, which is populated from National Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
473
6
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 466 publications
(516 citation statements)
references
References 24 publications
(12 reference statements)
29
473
6
3
Order By: Relevance
“…Finally, in agreement with previous findings at different stages of BCSP implementation (Logan et al, 2012;von Wagner, Baio, et al, 2011), we found significant regional differences in CRC uptake. Uptake was highest in the North East across all wealth quintiles and lowest in London, although in multivariate regression models we did not see significant differences between London, the South East, the South West, and the North West.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, in agreement with previous findings at different stages of BCSP implementation (Logan et al, 2012;von Wagner, Baio, et al, 2011), we found significant regional differences in CRC uptake. Uptake was highest in the North East across all wealth quintiles and lowest in London, although in multivariate regression models we did not see significant differences between London, the South East, the South West, and the North West.…”
Section: Resultssupporting
confidence: 93%
“…There is evidence of substantial variation in uptake by socio-economic status, with one study finding participation in the most deprived quintile of residential areas to be only 35%, compared with 61% in the least deprived quintile (von Wagner, Baio, et al, 2011). Previous studies have also shown systematic differences in CRC screening participation between geographical regions of England, with London and the North East reporting the lowest and highest rates of screening, respectively (Logan et al, 2012;von Wagner, Baio, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Our FIT positive rate was only 1.9% and this is again comparable to rates reported from other screening programs (Logan et al, 2012). Literature has reported rates of between 1 and 5%.…”
Section: Discussionsupporting
confidence: 74%
“…Among those invited for screening, only 66.9% returned their FIT, a participation rate that is comparable or better to what has been reported in the literature (Logan RF et al, 2012). However, in any screening program, it is very important to maximise the participation rate to reduce to impact of CRC.…”
Section: Discussionmentioning
confidence: 69%
“…This aligns with previous data that finds males are less likely to participate in CRC screening. 28,30,31 Given that males are more likely to be diagnosed and more likely to die from CRC, 32 interventions that specifically target males are needed. No other variables were significantly associated with being under-screened; however, this does not mean the other variables are not important.…”
Section: Variables Associated With Underscreeningmentioning
confidence: 99%